Coping Self‐Efficacy and Academic Stress Among Hispanic First‐Year College Students: The Moderating Role of Emotional Intelligence. Issue 3 (October 2016) - Watson, Joshua C.; Watson, April A.
Abstract : In this study, the authors examined the role that emotional intelligence plays in moderating the relationship between academic stress and coping self‐efficacy among a sample of 125 Hispanic 1st‐year college students enrolled at a medium‐size, southern Hispanic‐serving institution. Results of a 2‐stage hierarchical multiple regression analysis indicated that emotional intelligence was a significant moderator in the relationship for the students surveyed. Implications for counseling Hispanic 1st‐year college students and directions for future research are suggested.